Clinical Outcome of Noncardiac Surgery in Patients With History of Coronary Artery Revascularization by Percutaneous Coronary Intervention Versus Coronary Artery Bypass Graft Surgery. (3rd January 2018) - Park, Jungchan; Lee, Seung Hwa; Kim, Jeayoun; Park, Myungsoo; Gwon, Hyeon-Cheol; Tak Lee, Young; Maria Lee, Sangmin
Objective: Although safety concerns still remain among patients undergoing unanticipated noncardiac surgery after prior percutaneous coronary intervention (PCI), it has not been directly compared with coronary artery bypass grafting (CABG). The objective of this study was to compare clinical outcomes after noncardiac surgery in patients with prior (>6 months) coronary revascularization by PCI or CABG. Methods: From February 2010 to December 2015, 413 patients with a history of coronary revascularization, scheduled for noncardiac surgery were identified. Patients were divided into PCI group and CABG group and postoperative clinical outcome was compared between 2 groups. The primary outcome was composite of all-cause death, myocardial infarction, and stroke in 1-year follow-up. Results: The 413 patients were divided according to prior coronary revascularization types: 236 (57.1%) into PCI and 177 (42.9%) into CABG group. In multivariate analysis within 1-year follow-up, there was no significant difference in clinical outcome which was composite of all-cause death, myocardial infarction, and stroke (hazard ratio [HR]: 1.50; 95% confidence interval [CI]: 0.76-2.93; P  = .24). The same result was present in propensity-matched population analysis (HR: 1.43; 95% CI: 0.68-3.0; P  = .34). Conclusions: In patients undergoing noncardiac surgery with prior coronary revascularization by PCI or CABG performed on an average of 42 months after PCI and 50 months after CABG, postoperative clinical outcome at 1-year follow-up is comparable.